EVALUASI HASIL BELAJAR MENGGAMBAR DAN MENDESAIN MESIN ANTARA TARUNA DARI INPUT SMA DAN INPUT SMK DENGAN METODE KELOMPOK-KELOMPOK KECIL JURUSAN TEHNIKA DI PIP SEMARANG - Dwi Prasetyo (Politeknik Ilmu Pelayaran Semarang, 2018)
The purpose of this study was to determine the evaluation of learning outcomesEngineering Drawing and Design between cadets of Input SMA and SMK Input MethodSmall Group Programs Technical in PIP Semarang. The results of this study it can beconcluded that there are differences in the evaluation of learning outcomes between drawingand designing machines SMA Cadets input and input from SMK with a small group ofsubjects Technical method in PIP Semarang. The average value for the experimental group 1(input from SMA) is 74.2, while the average value for the experimental group 2 (input fromSMK) is 76.7. This means learning outcomes experimental group 2 was better than theexperimental group 1. But overall learning outcomes Youth in drawing and designing theengine is increased.